2020
DOI: 10.1039/d0nh00300j
|View full text |Cite|
|
Sign up to set email alerts
|

Controlled functionalization of carbon nanodots for targeted intracellular production of reactive oxygen species

Abstract: Multifunctional carbon nanodots with deep-red emission were prepared. These carbon nanodots are suitable for targeted intracellular production of reactive oxygen species by laser irradiation leading to efficient cancer cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 66 publications
(47 reference statements)
1
38
0
Order By: Relevance
“…In the cell lines which expressed folic acid receptors, S-doped CDs with folic acid conjugated surfaces ( 1 O 2 QY 0.4) showed targeted intracellular production of ROS upon irradiation at 660 nm. [136] To overcome the hypoxic tumor microenvironment and prevent rapid consumption of oxygen in PDT, Jia and coworkers synthesized Mn-doped CDs and assembled them with the aid of PEG, [59] which could produce 1 O 2 with a QY of 0.4, and catalyze generation of oxygen from H 2 O 2 . They were able to act as in situ tumor oxygenerator to ameliorate tumor hypoxia and hence to enhance the PDT efficacy.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…In the cell lines which expressed folic acid receptors, S-doped CDs with folic acid conjugated surfaces ( 1 O 2 QY 0.4) showed targeted intracellular production of ROS upon irradiation at 660 nm. [136] To overcome the hypoxic tumor microenvironment and prevent rapid consumption of oxygen in PDT, Jia and coworkers synthesized Mn-doped CDs and assembled them with the aid of PEG, [59] which could produce 1 O 2 with a QY of 0.4, and catalyze generation of oxygen from H 2 O 2 . They were able to act as in situ tumor oxygenerator to ameliorate tumor hypoxia and hence to enhance the PDT efficacy.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…Although original CNDs showed good water dispersibility, some aggregation was however observed in a pH range of 3−10 over a period of 24 h, probably due to strong H‐bonding interactions (Figure S4, Supporting Information). [ 12 ] We also found that the zeta potential of CNDs becomes more negative at pH > 9.0, because the network of hydrogen bonds between CNDs likely starts to disintegrate in more basic conditions, leading to the formation of a higher number of isolated nanodots. [ 25 ] In contrast, we did not observe any aggregation phenomenon in MCND samples in a broad pH range of 3−12 (Figure S5, Supporting Information), even for high concentration of MCNDs (up to 100 μg mL −1 ).…”
Section: Resultsmentioning
confidence: 91%
“…Based on our previous work, [ 12 ] carboxyl‐rich CNDs were first synthesized by a hydrothermal method using a conjugated polymer, polythiophene phenylpropionic acid (PPA), as the carbon source ( Scheme , Step I). A short amine‐terminated triethylene glycol (TEG) chain was chosen as a linker to connect CNDs with FA and Ce6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the CDs inducing the ROS generation have been reported in a lot of researches. 17,[30][31][32] Therefore, in the future work, we need to conduct further experiments to conrm this speculation.…”
Section: Comparisons Of Other Cds For Antibacterialmentioning
confidence: 99%